2005
DOI: 10.1111/j.1365-2842.2005.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of signs and symptoms of temporomandibular disorders in very old subjects

Abstract: Previous studies on the prevalence of signs of temporomandibular disorders (TMD) in elderly people have used non-standardized and invalidated examination protocols. The prevalence of the different signs of TMD in this group is therefore still unclear. The aim of this study was to evaluate the prevalence of signs of TMD in subjects of advanced aged, using a standardized and validated examination protocol. Additionally, young subjects were examined as a control group. Fifty-eight old peoples' home inhabitants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
2
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 20 publications
9
74
2
13
Order By: Relevance
“…In contrast, in a study by Pow et al (18) , higher percentage of severe TMD (18.3%) was observed for the group over 55 years of age. Moreover, it is worth mentioning that there is a trend towards diminished signs and symptoms of TMD with the advancement of age -as verified by Schmitter et al (19) . These authors compared two groups -one of elderly persons (68 to 96 years of age) and another of adults (18 to 45 years of age) -and obtained higher sensitivity to pain with palpation of the TMJ and masticatory Caption: COP = center of pressure; V ap = anteroposterior sway velocity; V ml = medial/lateral sway velocity; F ap = anteroposterior sway frequency; F ml = medial/lateral sway frequency.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, in a study by Pow et al (18) , higher percentage of severe TMD (18.3%) was observed for the group over 55 years of age. Moreover, it is worth mentioning that there is a trend towards diminished signs and symptoms of TMD with the advancement of age -as verified by Schmitter et al (19) . These authors compared two groups -one of elderly persons (68 to 96 years of age) and another of adults (18 to 45 years of age) -and obtained higher sensitivity to pain with palpation of the TMJ and masticatory Caption: COP = center of pressure; V ap = anteroposterior sway velocity; V ml = medial/lateral sway velocity; F ap = anteroposterior sway frequency; F ml = medial/lateral sway frequency.…”
Section: Discussionmentioning
confidence: 73%
“…However, other authors reported that the elderly can often suffer from TMD, but do not complain because they are more concerned with other overall health issues or more painful and debilitating diseases, leaving aside the symptoms related to the masticatory system (18) . This study showed a high prevalence of TMD in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is often diagnosed by observation of symptoms that are very subjective. Identification of these symptoms depends on cognitive ability, which varies widely both individually and among groups (15)(16)(17)(18) . According to Schmitter et al (18) , the elderly population presents a higher prevalence of objective signs of TMD; however, they rarely complain of pain.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,42,45 However, this is not the most appropriate method to understand the level of severity. Thus, we used the ProDTMMulti previously constructed to standardize the records about the signs and symptoms of patients in multidisciplinary clinics, and to identify what are the signs and symptoms that affect the patient and their severity, and what are the most critical conditions on a daily basis.…”
Section: Habitsmentioning
confidence: 99%